Kegiatan “Kamis Mlipis” Pembiasaan Bertutur Bahasa Jawa Sebagai Upaya Pembentukan Nilai Karakter Sopan Santun - Nurini Nurini (Adi Karsa: Jurnal Teknologi Komunikasi Pendidikan, 2025)
The opinion of people "Jowo ilang Jawane" is often heard among our community. This is a specialconcern for us, especially in the school education environment. Based on this, we need to carry outactivities so that this assumption does not actually become a reality regarding Javanese people who do not know and are able to speak Javanese and have lost the "unggah ungguh" manners within the scope of Javanese cultural treasures. The aim of this research describe the application of cultural habituation to speak Javanese as a form of character values formation. The method used is descriptive qualitative with observation and interview techniques. The results of the research show that the implementation of the habit of speaking Javanese has a positive impact by raising religious values, politeness, tolerance and love of peace. From this research can be concluded that one way to foster the character value of good manners is through daily habituation activities in the school environment.